EMOTIONAL INTELLIGENCE AND ACADEMIC ACHIEVEMENT OF STUDENTS: A REVIEW OF VAN ROOY AND VISWESVARAN’S (2004) - Quini, Megha; David, Shine (International Journal of Research -GRANTHAALAYAH, 2025)
This paper reviews the influential meta-analysis by Van Rooy and Viswesvaran (2004), which systematically examined the predictive validity and nomological net of emotional intelligence (EI). The study aimed to clarify the conceptual status of emotional intelligence (EI) in psychological literature by analyzing its relationship with cognitive intelligence, personality, and job performance. Using data from 69 studies involving over 7,000 participants, the authors found moderate correlations between emotional intelligence (EI) and both cognitive ability and personality traits. More importantly, EI showed incremental validity in predicting job performance beyond these traditional constructs. This review summarizes their methodology, key findings, and implications, and discusses the study’s relevance in the context of ongoing debates on EI’s theoretical foundation and practical applications.